Building better biochronology: New fossils and 40 Ar/ 39 Ar radioisotopic dates from Central Anatolia - Andrew Tholt; Okşan Başoğlu; Yener Bektaş; Raymond Bernor; Joshua P. Carlson; Ömer Dağ; Uğur Doğan; Ahmet Cem Erkman; Ferhat Kaya; Nuretdin Kaymakçı; Pınar Gözlük Kırmızıoğlu; Maud J. M. Meijers; et al. (Proceedings of the National Academy of Sciences, 2025)
Türkiye’s geographic position between Europe, Asia, and Africa gives it pivotal importance for understanding the local, interregional, and intercontinental dynamics of Neogene vertebrate evolution. Although rich in vertebrate fossil deposits spanning the Middle and Late Miocene, associated geochronology has been limited by the lack of available volcanic materials that allow radioisotopic dating and geochemical correlation. As a result, calibrating mammalian evolution has been largely restricted to the semicircular application of paleomagnetic inferences combined with temporally ill-constrained and geographically remote biochronological deductions. For example, fossils from three Greek localities and one Anatolian locality assigned to the primate genus Ouranopithecus lack datable samples, leaving its ages poorly constrained. Chronological calibration based on the 40 Ar/ 39 Ar results reported here demonstrates how a fauna-focused, precision geochronology can enhance a better understanding of evolving species lineages and the ecosystems they comprise.